2018
DOI: 10.1016/j.cognition.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing languages from dialects: A litmus test using the picture-word interference task

Abstract: Linguists have been working to develop objective criteria for distinguishing languages from dialects for well over half a century. The prevailing view amongst sociolinguists is that no objective criteria can be formulated. The aim of this study is to examine whether language processing can provide insights into this problem by comparing bidialectal behavioural effects to bilingual effects reported in the literature. Previous research has demonstrated that when bilinguals name an object in Lx while simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 60 publications
3
32
1
Order By: Relevance
“…One recent example is Kirk et al ( 2018 ), who showed that speakers of Scottish English performed similar to bilingual speakers in a switching task involving switching between the local dialect and standard English, indicating that at least on a lexical level, bidialectals show similar behavior as bilinguals. However, Melinger ( 2018 ) found no trace of language separation in a Scottish English population in a picture-word interference task. Both of these studies looked for signs of bilingualism in the lexicon.…”
Section: Introductionmentioning
confidence: 99%
“…One recent example is Kirk et al ( 2018 ), who showed that speakers of Scottish English performed similar to bilingual speakers in a switching task involving switching between the local dialect and standard English, indicating that at least on a lexical level, bidialectals show similar behavior as bilinguals. However, Melinger ( 2018 ) found no trace of language separation in a Scottish English population in a picture-word interference task. Both of these studies looked for signs of bilingualism in the lexicon.…”
Section: Introductionmentioning
confidence: 99%
“…The observed register-switch costs also indicate that lexical representations contain tags for register membership, since language-switch costs are typically explained with mental representations of language membership, such as language tags (e.g., Green, 1998) or language nodes (Grainger, Midgley & Holcomb, 2010). Yet, we note that the only study of speech register processing known to us concluded that register (and dialect) membership are represented differently from language membership (Melinger, 2018). Melinger (2018) found that, in a picture-word interference experiment, distractors belonging to different speech registers (and different dialects) produced interference effects, differently from the facilitation produced by translation-equivalent distractors in the studies of Costa and colleagues (Costa & Caramazza, 1999; Costa, Miozzo & Caramazza, 1999).…”
Section: Discussionmentioning
confidence: 67%
“…Yet, we note that the only study of speech register processing known to us concluded that register (and dialect) membership are represented differently from language membership (Melinger, 2018). Melinger (2018) found that, in a picture-word interference experiment, distractors belonging to different speech registers (and different dialects) produced interference effects, differently from the facilitation produced by translation-equivalent distractors in the studies of Costa and colleagues (Costa & Caramazza, 1999; Costa, Miozzo & Caramazza, 1999). Due to this conflicting evidence, it is unclear at the moment whether register membership is tagged to lexical entries.…”
Section: Discussionmentioning
confidence: 67%
“…Ultimately, the present results demonstrate that it is possible and necessary for the relatively small fields of research on the acquisition of regional dialects (Nycz, 2013) and processing differences between languages versus dialects (Melinger, 2018) to expand to also consider prosody. They also suggest the need to adapt psycholinguistic models that have overwhelmingly been developed for words and phonemes in research on second language (L2) processing (Keatley, 1992;Fig.…”
Section: Discussionmentioning
confidence: 75%